Effect of Emotional Self-Regulation Strategies and Systematic Desensitization on Stress Level of Adult Dental Patients: A Clinical Trial - M Parivar; A Rezaie; J Babapor (Islamic Azad University, 2023)
Background and Aim: This study aimed to compare the effects of emotional self-regulation strategies and systematic desensitization on stress level of adult dental patients.   Materials and Methods: The study population included 40 adult dental patients that were selected by purposeful sampling and were classified into two experimental groups of emotional self-regulation strategy (n=20) and systematic desensitization (n=20). Data were collected using a stress questionnaire. The experimental groupsreceived 8 sessions of 90-minute emotional self-regulation strategy and desensitization instructions. Data were analyzed by t-test and paired t-test. Results: Emotional self-regulation and systematic desensitization affected the stress level of adult dental patients. However, there was no significant difference between the effects of emotional self-regulation and systematic desensitization on stress levels of adult dental patients (P>0.05). Conclusion: Emotional self-regulation and systematic desensitization instructions equally affected the stress level of adult dental patients in this study.